Security and Public Health - Sidel, Victor W. (Social justice, 2002)
Part of a special issue on global threats to security. The writers examine how public health and security are intertwined and outlines specific aspects of security as they relate to public health. Focusing on nuclear security, biological security, and global security, they consider how basic public health principles can be applied to improving security in order to assure the conditions in which people can be healthy.